The cloud at your service : the when, how, and why of enterprise cloud computing - Rosenberg, Jonathan B., 1956-; Mateos, Arthur (Greenwich, Conn. : Manning, 2011)
A guide to cloud computing covers such topics as building scalable applications, migrating existing IT to the cloud, and cloud data security.
What is cloud computing? -- Understanding cloud computing classifications -- The business case for cloud computing -- Security and the private cloud -- Designing and architecting for cloud scale -- Achieving high reliability at cloud scale -- Testing, deployment, and operations in the could -- Practical considerations -- Cloud 9: the future of the cloud.
Includes bibliographical references and index.
Keywords: Cloud computing; Application software -- Design